A conditional suicide system in Escherichia coli based on the intracellular degradation of DNA. - Ahrenholtz, I (1994)
The potential risks associated with the intentional or unintentional release of genetically engineered microorganisms led to the construction of biological containment systems by which bacteria are killed in a controlled suicide process. In previously published suicide systems, cell killing was caused by proteins destroying the cell membrane or cell wall. Here a conditional cell killing system based on the intracellular degradation of cellular DNA is presented. The nuclease gene used was that of the extracellular nuclease of Serratia marcescens. The nuclease gene was deleted for the leader-coding sequence, and the truncated gene was put under the control of the lambda pL promoter. Following thermoinduction of the nuclease gene cassette in Escherichia coli, cell survival dropped to 2 x 10(-5), and more than 80% of the radioactively labeled DNA was converted to acid-soluble material within 2.5 h in the absence of cell lysis. The majority (84%) of clones which survived thermoinduced killing turned out to be as sensitive to a second thermoinduction as the original strain. The other clones showed somewhat slower killing kinetics or slightly higher final levels of survivors. The suicide system described combines the regulated killing of cells with the destruction of intracellular DNA otherwise potentially available for horizontal gene transfer processes.